Biocatalytic cascades and intercommunicated biocatalytic cascades in microcapsule systems. Issue 25 (1st June 2022) - Zhang, Pu; Fischer, Amit; Ouyang, Yu; Wang, Jianbang; Sohn, Yang Sung; Karmi, Ola; Nechushtai, Rachel; Willner, Itamar
Abstract : Dynamic dimerization of GOx-loaded microcapsules with β-gal//hemin/G-quadruplex-bridged T1 /T2 -loaded microcapsules guides the bi-directional intercommunication of the three catalysts cascade. Abstract : Biomolecule-loaded nucleic acid-functionalized carboxymethyl cellulose hydrogel-stabilized microcapsules (diameter ca. 2 μm) are introduced as cell-like containments. The microcapsules are loaded with two DNA tetrahedra, T1 and T2, functionalized with guanosine-rich G-quadruplex subunits, and/or with native enzymes (glucose oxidase, GOx, and/or β-galactosidase, β-gal). In the presence of K + -ions and hemin, the T1 /T2 tetrahedra constituents, loaded in the microcapsules, assemble into a hemin/G-quadruplex bridged tetrahedra dimer DNAzyme catalyzing the oxidation of Amplex Red to Resorufin by generating H2 O2 . In the presence of co-loaded GOx or GOx/β-gal, the GOx//T1 /T2 hemin/G-quadruplex cascade catalyzing the glucose-mediated oxidation of Amplex Red to Resorufin, and the three-biocatalysts cascade consisting of β-gal//GOx//hemin/G-quadruplex bridged T1 /T2 catalyzing the lactose-driven oxidation of Amplex Red to Resorufin proceed in the microcapsules. Enhanced biocatalytic transformations in the microcapsules, as compared to the performance of the reactions in a homogeneous phase, are observed, due to the proximity of the biocatalysts in a confined volume. As the synthetic methodology to prepare the microcapsules yields boundaries functionalized with complementary nucleic acid tethers, the dynamic association of different microcapsules, loaded selectively with biomolecular catalysts, proceeds. The dynamic dimerization of GOx-loaded microcapsules and hemin/G-quadruplex bridged T1 /T2 DNAzyme-loaded microcapsules yields effective intercommunicated microcapsules driving the GOx//hemin/G-quadruplex bridged T1 /T2 DNAzyme cascade. In addition, the dynamic dimerization of GOx-loaded microcapsules with β-gal//hemin/G-quadruplex bridged T1 /T2 -loaded microcapsules enables the bi-directional intercommunicated operation of the lactose-stimulated three catalysts β-gal//GOx//hemin/G-quadruplex bridged T1 /T2 DNAzyme cascade. The guided separation and formation of dynamic supramolecular dimer microcapsular containments, and the dictated switchable operation of intercommunicated biocatalytic cascades are demonstrated.